Ubiquitous learning in occupational health and safety for vocational education - Ketut Ima Ismara; Amin Suharjono; Didi Supriadi (International Journal of Evaluation and Research in Education (IJERE), 2021)
This research aimed to develop instructional media for occupational safety and health android-based for vocational schools. The second aim is to determine the feasibility of instructional media and student responses. The type of research is research and development (R&D) with the Analysis, Design, Development, Implementation, Evaluation (ADDIE) method, namely, analysis, design, development, implementation, and evaluation. The instrument used for data collection was a questionnaire with fourth scales. Data collection used an assessment questionnaire for two experts and 103 users. Research data analysis techniques used quantitative descriptive analysis. This study's results have produced products in the form of android-based instructional media for Occupational Safety and Health. In this study, we designed and developed an application called Zerosicks for mobile devices to help students learn occupational safety and health principles. The results of testing for all features and navigation work well and under their functions. The assessment results by content experts, media experts, and students as users indicate that this media has a very decent level of eligibility. Suggestions for product development are to add videos to the media, provide selected music, and add discussion forums for users.